2018
DOI: 10.3390/met8110877
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behaviour and Microstructural Characterization of VAT 36 and VAT 32 Superalloys

Abstract: Superalloys are used primarily for the aerospace, automotive, and petrochemical industries. These applications require materials with high creep resistance. In this work, evaluation of creep resistance and microstructural characterization were carried out at two new nickel intermediate content alloys for application in aerospace industry and in high performance valves for automotive applications (alloys VAT 32 and VAT 36). The alloys are based on a high nickel chromium austenitic matrix with dispersion of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…According to Oliveira et al . , the results of the creep test with nickel-based superalloy 625 suggested that the Considering creep mechanism at 675 ºC of VAT 32 (superalloys with intermediate nickel content different amounts of carbon, iron, titanium, and niobium) by Gobbi et al 10 , the stress exponent value is 13.72 and activation energy is 616 kJ/mol, results were correlated to formation of higher amount of carbides and intermetallic phases caused by higher mass percentage of carbon and different amounts of alloying elements.…”
Section: Creep Testmentioning
confidence: 98%
See 2 more Smart Citations
“…According to Oliveira et al . , the results of the creep test with nickel-based superalloy 625 suggested that the Considering creep mechanism at 675 ºC of VAT 32 (superalloys with intermediate nickel content different amounts of carbon, iron, titanium, and niobium) by Gobbi et al 10 , the stress exponent value is 13.72 and activation energy is 616 kJ/mol, results were correlated to formation of higher amount of carbides and intermetallic phases caused by higher mass percentage of carbon and different amounts of alloying elements.…”
Section: Creep Testmentioning
confidence: 98%
“…Nickel-based superalloys are known since the 1930s, and used primarily in aerospace applications [1][2][3][4] . These applications require a material with high mechanical strength 5,6 , good resistance to fatigue and creep [7][8][9][10] , good corrosion resistance 11 , and ability to operate continuously at elevated temperatures 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strict correlation between microstructural features is also of utmost importance for the development and application of other high-temperature alloys. Moving to steels and Ni-based alloys characterized by an austenitic matrix, the strengthening role played by carbides, other precipitates, or dispersoids, has been experimentally investigated in the temperature range of 675-750 • C by Gobbi et al [12] in the case of alloys VAT 32 and VAT 36. In the gamma prime-containing Ni-base superalloys, the creep resistance at high temperature is also affected by the presence of solute atoms in solid solution.…”
Section: Creep-microstructure Correlations For Specific Materials Classesmentioning
confidence: 99%
“…Usually, superalloys can operate at a high fraction of their melting point. Because of this, superalloys are used in jet engine components such as turbine blades and combustion chamber [6]. Oxide Dispersion Strengthening (ODS) superalloys have been researched in the last decades because the ODS superalloys have excellent high-temperature creep-rupture strength and resistance oxidation and corrosion is higher than those of the superalloys [7,8].…”
Section: Introductionmentioning
confidence: 99%